KINETICS OF RADIATION-INITIATED PROCESSES IN EPOXY ACCORDING TO EPR - Ismailova, G.A.; Sarsembinov, Sh.Sh.; Kupchishin, A.I.; Komarov, F.F. (Recent Contributions to Physics, 2008)
Kinetics of change of EPR spectrum are experimentally studied in epoxy irradiated  to the doses of 3 MGy and 6 MGy. Time dependences of internal friction characteristics associated with radiation-induced processes of epoxy scission and cross-linking  to comparison with  kinetics of change of EPR spectrum.